Trematode maturation patterns in a migratory snail host: What happens during upshore residency in a Mediterranean lagoon - Born-Torrijos, Ana; Raga, Juan Antonio; Holzer, Astrid S (Parasitology research, 2016)
Maturation of trematode larval stages is expected to be temporally and spatially adapted to maximise the encounter with the adequate downstream host, i.e. the host, which will be infected by this parasite stage. Since studies on intramolluscan parasite maturation are scarce but important in the context of parasite transmission, the larval development inside sporocysts was monitored during upshore residency of the snail host Gibbula adansonii (Trochidae), i.e., from March to May (2011 and 2013), when these snails temporarily reside in the intertidal habitat of a Western Mediterranean lagoon (40° 37' 35′′ N, 0° 44' 31′′ E, Spain). Data on the relative quantity of different maturation stages of Cainocreadium labracis and Macvicaria obovata (Opecoelidae) parasitising the G. adansonii as well as on snail and sporocyst size were explored using linear models and linear mixed models. The effect of the trematodes on snail growth was shown to be species-specific, with snail and sporocyst size acting as proxies of the reproductive capacity of M. obovata but not that of C. labracis. The number of cercarial embryos and germinal balls did not show monthly variation in either parasite species, but a higher number of mature stages and the highest maturity index was found in April. Hence, during the snail's limited spawning-related presence in the upshore waters of the lagoon, continuous production and output of infectious cercariae was observed, which indicates a link between larval maturation and snail migration. The synchronization of snails, mature parasite transmission stages and downstream hosts in time and space guarantees a successful completion of the life cycle.
Keywords: larva; hlemýždi; Snails; Animal Migration; mořská voda; Trematoda; Larva; zvířata; druhová specificita; interakce hostitele a parazita; roční období; Host-Parasite Interactions; Španělsko; Spain; stadia vývoje; Linear Models; Seawater; ekosystém; Species Specificity; Cercaria; cerkárie; Oocysts; Ecosystem; Seasons; Reproduction; rozmnožování; migrace zvířat; oocysty; Animals; lineární modely; Life Cycle Stages